Efeitos do sombreamento na produção de matéria seca, valor nutritivo, morfologia e anatomia de azevém em sistemas agroflorestais - Pilau, Janine (2014)
The objectives of this study were to quantify the meteorological elements in agroforestry system (AFS) and full sun, to analyze the evaluate the leaf area, percentage of leaves and stems, quantify the production of dry matter (DM) and crude protein (CP) of annual ryegrass grown in the understory of canafístula and eucalyptus. In addition to evaluating the anatomic changes completely expanded ryegrass leaves resulting from acclimatization of this species to shading of angico-vermelho and canafístula. The experiment was conducted in an area that has an agroforestry system (AFS). Forest species are distributed in range and line, where the rows are separated on 12 and 6 meters respectively. The experiment was conducted in a randomized block design with three replications in split splot scheme. The ryegrass was sown in the understory of the forest species and full sun on 05/06/2012. The weather data were measured on AFS and in full sun for the purpose of characterization of production environments. For measurements of leaf area, relating the percentage of leaves and stems, quantify the production of DM and determine CP content of six cuts with box 0.25 m2 were performed in each of the treatments. To evaluate the effect of shading on the anatomy of leaves of annual ryegrass, samples of fully expanded leaf blades were collected from all treatments. In AFS s, range and line, there was no significant difference in the percentage photosynthetically active radiation transmited (PARt) and transmission with only relative to full sun. Among species, the PARt was reduced by approximately 30%. The air temperature (T°) showed variation between the AFS compared to full sun during the ryegrass development cycle. Shading caused by the presence of forest species, eucalyptus and canafístula in AFS, range and line, did not limit the growth and development of ryegrass grown in shaded understory. Independent of the systems used, the DM production of ryegrass and CP content, reached satisfactory levels for the use of this species as alternative forage in AFS. The leaf anatomy of Lolium multiflorum Lam cv. Common, is influenced by the environmental conditions in which it develops. Annual ryegrass can be used to compose Agroforestry Systems.